(untitled) (Research, Society and Development, 2021)
The objective is to analyze conditions of access to the Internet by adolescents from state schools in Curitiba (PR), and to identify inequalities according to the demographic characteristics of students and income from school neighborhood. Associations between access conditions and income were investigated by: 1) multilevel logistic regression models to estimate odds ratios (OR) and 95% confidence intervals (95% CI); and 2) Moran Global and local indexes. In schools, 1,232 students completed the questionnaire. The most frequent Internet access device was the cell phone (75.4%), followed by the computer (27.3%) and tablet (8.4%); 81.0% reported accessing internet at home, 25.1% wi-fi networks; 77.2% are related to daily access and 53.1% have their own device. The odds of accessing the Internet by cell phone (OR 1.94 95% CI 1.25; 3.01), daily (OR 3.37; 95% CI 1.38; 8.20) and with own devices (OR 1, 81 95% CI 1.00-3.27) increased with increase of school neighborhood income, while computer use was lower in higher income tertiles (OR 0.61 95% CI 0.41; 0.91). There was an inverse spatial correlation between income and use of cell phone (-0.26) and tablet (-0.29), and positive for computer (0.31) and daily internet use (0.30). We found inequalities in the conditions of access to the Internet with students and income characteristics.